Dielectric assist accelerating structures for compact linear accelerators of low energy particles in hadrontherapy treatments - Martinez-Reviriego, Pablo; Esperante, Daniel; Grudiev, Alexej; Gimeno, Benito; Blanch, César; González-Iglesias, Daniel; Fuster-Martínez, Nuria; Martín-Luna, Pablo; Martínez, Eduardo; Menendez, Abraham; Fuster, Juan (Frontiers in Physics, 2024)
Dielectric Assist Accelerating (DAA) structures based on ultralow-loss ceramic are being studied as an alternative to conventional disk-loaded copper cavities. This accelerating structure consists of dielectric disks with irises arranged periodically in metallic structures working under the TM02-π mode. In this paper, the numerical design of an S-band DAA structure for low beta particles, such as protons or carbon ions used for Hadrontherapy treatments, is shown. Four dielectric materials with different permittivity and loss tangent are studied as well as different particle velocities. Through optimization, a design that concentrates most of the RF power in the vacuum space near the beam axis is obtained, leading to a significant reduction of power loss on the metallic walls. This allows to fabricate cavities with an extremely high quality factor, over 100,000, and shunt impedance over 300 MΩ/m at room temperature. During the numerical study, the design optimization has been improved by adjusting some of the cell parameters in order to both increase the shunt impedance and reduce the peak electric field in certain locations of the cavity, which can lead to instabilities in its normal functioning.